Religion matters: an introduction to the world's religions - Prothero, Stephen R. (W.W. Norton & Company, 2020)
"Stephen Prothero's Religion Matters builds religious literacy through an expert's introduction to the greatest stories ever told. Religions are systems of stories, and there is no better way to engage with the world's religions than through the stories that animate their beliefs and practices. Through the exploration of these ancient histories, texts, and stories and their continuities today, Stephen Prothero, a New York Times bestselling author, gifted storyteller, and award-winning scholar and teacher, helps students grasp both the vibrancy of the great religions and their role in our fractured world. Covering Hinduism, Buddhism, Sikhism, Judaism, Christianity, Islam, Daoism, Confucianism, Navajo Religion, and Atheism, this book focuses on what makes each religion distinct without neglecting the connections between them"--